Iatrogenic pulmonary fat embolism after surgery in a patient with fatty liver - Mitrović, Dragan; Lazarević, Svetlana (Vojnosanitetski pregled, 2021)
Introduction. Fat embolism refers to the presence of fat globules in the lung parenchyma and its peripheral circulation. Obstruction of the lung vessels by fat emboli can lead to acute cor pulmonale when the compensatory capabilities of the pulmonary vasculature are exceeded. Case report. We presented a case of a 78-year old man who suffered a dissection of abdominal aortic aneurysm. Urgent surgical procedure was performed and aneurysm replaced with aorto-bifemoral bypass grafting using a Dacron graft. Despite the procedure the patient died the following day. The autopsy revealed that the cause of death was hypovolemic shock. There were no bone fractures (also no fractures of ribs and sternum from cardiopulmonary resuscitation) or injuries of the subcutaneous fat tissue or other organs (besides those from the surgery). However, additional autopsy findings included fatty liver change, small liver hemorrhages (confirmed microscopically), as well as a presence of fat droplets in the hepatic veins, as well as in the pulmonary vessels, i.e. pulmonary fat embolism [confirmed with hematoxylin/eosin (H/E), and Sudan III staining], which could be the contributing cause of death. Conclusion. The presented case indicates that pulmonary (or even systemic) fat embolism should be considered as the possible iatrogenic cause of unexpected and unexplained death in the cases where elective surgical procedures were performed in patients with fatty liver change. Pathologists must be aware of this possibility, since it is not easily recognized on routine H/E staining, and some of the special staining technique should be applied.
Keywords: embolism, fat; aneurysm, ruptured; postoperative complications; pulmonary embolism; fatty liver; diagnosis, differential; death